The effect of post-sintering treatments on the fatigue and biological behavior of Ti-6Al-4V ELI parts made by selective laser melting. (July 2017) - Benedetti, M.; Torresani, E.; Leoni, M.; Fontanari, V.; Bandini, M.; Pederzolli, C.; Potrich, C.
Abstract: Fatigue resistance and biocompatibility are key parameters for the successful implantation of hard-tissue prostheses, which nowadays are more and more frequently manufactured by selective laser melting (SLM). For this purpose, the present paper is aimed at investigating the effect of post-sintering treatments on the fatigue behavior and biological properties of Ti samples produced by SLM. After the building process, all samples are heat treated to achieve a complete stress relief. The remaining ones are tribofinished with the aim of reducing the surface roughness of the as-sintered condition. Part of the tribofinished samples are then subjected to one of the following post-sintering treatments: (i) shot peening, (ii) hot isostatic pressing (HIP), and (iii) electropolishing. It is found that shot peening and HIP are the most effective treatments to improve the high and the very-high cycle fatigue resistance, respectively. At the same time, they preserve the good biocompatibility ensured by the biomedical Titanium Grade 23.